(untitled) (Research, Society and Development, 2023)
Breast cancer is the most common pathology among women in Brazil and in the world, responsible for high mortality rates, and considered a major public health problem. Breast cancer has several tumor markers that can be found at different stages of tumor development from the beginning to possible recurrences. Tumor biomarkers are used for the differential diagnosis in symptomatic patients, clinical staging, establishment of the diagnosis, monitoring of therapeutic efficiency, location of metastases, treatment by immunoradiotherapy and early detection of recurrence. Therefore, a narrative bibliographic review was carried out in order to demonstrate the importance of biomarkers, consulting publications available in the main databases such as Google Scholar, PubMed, SciELO, as well as articles published by INCA. 22 articles were selected that contributed to the conclusion of the study, which show the great importance of tumor biomarkers in the evaluation of the tumor since it is discovered until its reappearance, being able to evaluate the prognosis, degree of staging, treatment and later to monitor its effectiveness.